Peran Dinas Pendidikan Povinsi Sumatra Utara dalam Upaya Pengembangan Sekolah Luar Biasa Negeri Autis - Br Manurung, Rani R; Nst, Irwan; Musthafa, Walid (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2021)
This research is motivated by the search for the number of children with special needs, so that the number of Special Schools (SLB) has also increased and has been established in almost every district / city. From the above statement, it does not make the role of the North Sumatra Province education office complete, because the problem of education in special schools (SLB) is not only related to quantity but also quality. This means that the Education Office should also have a role in the development of Special Schools both in State Special Schools (SLB) and private Special Schools (SLB), as efforts to improve SLB can also have good quality. The data research method in this research is using observation, documentation and interview methods and then the data is collected. From the results of this study, it can be seen that the role of the North Sumatra Provincial Education Office in the Development Effort for the Autistic State Special School (SLB) is to coordinate, supervise and strive for better service management, monitor and report the performance of school principals and teacher performance, policies, operational policies for the level of education of children with special needs and equal distribution of educatio n for children with special needs, socializing with parents or the community that children with special needs are very important to get education.